Transmissible Veneral Tumor (TVT) in a Cross Breed Female Pitbull - Piúma Gonçalves, Helena; Waller, Stefanie; Versteg, Nielle; M. Meinerz, Ana Raquel; T. França, Raqueli; Brum Cleff, Marlete (Brazilian Journal of Case Reports, 2021)
Not applicable.